Unlocking Potential With Multimodal Learning and Assessment: A Discussion of the Barriers and Benefits - White, Jonathan Paul (GILE Journal of Skills Development, 2024)
In the current dynamic education landscape, equipping students with flexible, critical and creative digital literacy skills is essential. Higher education plays a key role in this endeavour, as changes in the use of digital technology and academic practices have created an increasing need for teachers and students to develop multimodal competencies. To develop these skills, educational institutions should embrace and utilise multimodality in both teaching and assessment. Aside from meeting students’ expectations to develop their digital literacy skills, multimodal approaches provide an engaging, interactive and creative experience of education. They also constitute a more inclusive method of learning, as neurodivergent students can access information and demonstrate knowledge in different ways. This article provides a synthesis of research into the barriers and benefits of multimodal learning and assessment. The paper calls for a change in mindset among education stakeholders, advocating for the recognition of learning as multimodal, and the implementation of multimodal assessment.